Nest material preferences by spotless starlings. (21st October 2017) - Ruiz-Castellano, Cristina; Tomás, Gustavo; Ruiz-Rodríguez, Magdalena; Soler, Juan J
Abstract : Birds may prefer materials with antimicrobial and antiparasitic properties for building their nests, and we experimentally tested and found support for this hypothesis in a population of spotless starlings. Within the offered material, birds preferred unpigmented feathers and aromatic plants for building their nests, which are those that the literature describes with higher antimicrobial properties. Abstract: The avian nest is an essential structure for offspring development. For adults, nest building entails costs in terms of time, energy, and exposure to predators and parasites. Amount and diversity of materials used for nest building depend on their availability and functionality in scenarios of sexual selection and parasitism. Green plants and feathers of different colors have been hypothesized to play key roles in offspring protection against pathogens, and we here experimentally assessed spotless starling ( Sturnus unicolor ) preferences for pigmented versus unpigmented feathers and for different green plants (aromatic vs. non-aromatic plants) as nest materials. We predicted a preferential selection of unpigmented feathers and aromatic plants according to the antimicrobial properties of these materials described in the literature. We evaluated these predictions during nest building and during egg-laying stages. As expected, starlings preferentially selected unpigmented feathers both before and during egg laying, while aromatic plants were preferentially selected only during the egg-laying stage. These results suggest that starlings prefer nest materials that enhance antimicrobial protection of their offspring. We also discuss some other, non-exclusive functions that might explain the observed preference for nest materials, especially with regard to their potential role in sexual signaling.